3D Fluid-Attenuated Inversion Recovery Imaging: Reduced CSF Artifacts and Enhanced Sensitivity and Specificity for Subarachnoid Hemorrhage - Lummel, N.; Schoepf, V.; Burke, M.; Brueckmann, H.; Linn, J. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: FLAIR images are highly sensitive for SAH. However, CSF flow artifacts caused by conventional FLAIR can produce false-positive results. Here, we compare 3D and 3D FLAIR sequences, focusing on their potential for containing these artifacts and their sensitivity and specificity for detection of SAHs. MATERIALS AND METHODS: We evaluated the following 4 FLAIR sequences: 1) 2D FLAIR at 1.5T, 2) 2D FLAIR, 3) 2D PROPELLER-FLAIR, and 4) 3D Cube-FLAIR at 3T. All sequences were performed in 5 healthy volunteers; sequences 2 and 4 were also performed under routine conditions in 10 patients with focal epilepsy and in 10 patients with SAH. Two neuroradiologists independently conducted the analysis. The presence of flow artifacts in the ventricles and cisterns of healthy volunteers and patients with epilepsy was evaluated and scored on a 4-point scale. Mean values were calculated and compared by using paired t tests. Sensitivity and specificity for SAH detection in sequences 2 and 4 were determined. RESULTS: Cube-FLAIR showed almost no CSF artifacts in the volunteers and the patients with epilepsy; therefore, it was superior to any other FLAIR (P < .001). Sensitivity and specificity of SAH detection by 3T FLAIR were 58.3% and 89.4%, respectively, whereas Cube-FLAIR had a sensitivity of 95% and a specificity of 100%. CONCLUSIONS: Cube-FLAIR allows FLAIR imaging with almost no CSF artifacts and is, thus, particularly useful for SAH detection. CIconfidence intervalGREgradient-recalled echoPROPELLERperiodically rotated overlapping parallel lines with enhanced reconstructionSEstandard error